2021
DOI: 10.5187/jast.2021.e109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus-based probiotics on growth performance, nutrient digestibility, and intestinal health of weaned pigs

Abstract: Effects of Bacillus-based probiotics on growth performance, nutrient digestibility, and intestinal health of weaned pigs Running Title (within 10 words)Effects of dietary probiotics on weaned pig health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 56 publications
4
27
0
Order By: Relevance
“…The dietary supplementations with B. subtilis and B. licheniformis were expected more effective in weanling pigs than in growing pigs where they are under the development or impairment of gut microbiota [ 41 ]. Similar to our results, the study of Mun et al [ 42 ] showed a tendency to improve digestibility of CP with supplementation of B. licheniformis and B. subtilis complex in weanling pigs. Lee et al [ 30 ] also reported the positive effects on ATTD of DM and CP in weanling pigs.…”
Section: Discussionsupporting
confidence: 92%
“…The dietary supplementations with B. subtilis and B. licheniformis were expected more effective in weanling pigs than in growing pigs where they are under the development or impairment of gut microbiota [ 41 ]. Similar to our results, the study of Mun et al [ 42 ] showed a tendency to improve digestibility of CP with supplementation of B. licheniformis and B. subtilis complex in weanling pigs. Lee et al [ 30 ] also reported the positive effects on ATTD of DM and CP in weanling pigs.…”
Section: Discussionsupporting
confidence: 92%
“…Since the ban on the use of antibiotics as animal growth promoters, the use of probiotics in livestock production has been steadily on the rise [12,13]. In swine production, the most common probiotic species used are Lactobacillus, Bacillus, Clostridium, Bifidobacterium, Enterococcus, and Saccharomyces [16,[164][165][166]. To date, there is abundant evidence demonstrating the beneficial effects of probiotics on swine health and growth.…”
Section: Influence Of Probiotics Supplementation On Mi-crobial Metabo...mentioning
confidence: 99%
“…Chromium oxide (Cr 2 O 3, 2 g/kg) was added to the diets as an indigestible marker to measure digestibility [12]. Pigs were fed diets mixed with chromium oxide for 4 consecutive days from d 4 and d 11, fresh excreta samples were collected in that period.…”
Section: Nutrient Digestibilitymentioning
confidence: 99%